2013
DOI: 10.1002/da.22169
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Traumas and Risk Thresholds: 12-Month PTSD in the World Mental Health (Wmh) Surveys

Abstract: Background Clinical research suggests that posttraumatic stress disorder (PTSD) patients exposed to multiple traumatic events (TEs) rather than a single TE have increased morbidity and dysfunction. Although epidemiological surveys in the United States and Europe also document high rates of multiple TE exposure, no population-based cross-national data have examined this issue. Methods Data were analyzed from 20 population surveys in the World Health Organization World Mental Health Survey Initiative (n 51,295… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
247
6
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 377 publications
(290 citation statements)
references
References 38 publications
22
247
6
3
Order By: Relevance
“…The authors tentatively termed these conditions ‘cumulative’ versus ‘multiple’ PTSD. These assumptions were supported by the results of a large cross-national, population-based survey (Karam et al, 2014), which found not only that respondents with PTSD who had been exposed to multiple traumas had a higher probability of PTSD, but also that nearly 20% of these respondents attributed their current PTSD symptoms to more than one traumatic event. The practice of choosing a single traumatic event in individuals with multiple trauma exposure does not account for these cumulative effects of multiple traumas.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The authors tentatively termed these conditions ‘cumulative’ versus ‘multiple’ PTSD. These assumptions were supported by the results of a large cross-national, population-based survey (Karam et al, 2014), which found not only that respondents with PTSD who had been exposed to multiple traumas had a higher probability of PTSD, but also that nearly 20% of these respondents attributed their current PTSD symptoms to more than one traumatic event. The practice of choosing a single traumatic event in individuals with multiple trauma exposure does not account for these cumulative effects of multiple traumas.…”
Section: Introductionmentioning
confidence: 87%
“…Kessler et al, 2017, 1995; Smith, Summers, Dillon, & Cougle, 2016). Besides the type of trauma, numerous studies have found that cumulative trauma, mostly defined as the number of different trauma types, is associated with greater PTSD risk and symptom severity (Green et al, 2000; Karam et al, 2014; Wilker et al, 2015). Simpson, Comtois, Moore, and Kaysen (2011) found that the prevalence of PTSD increased from 53.7% to 67.2% when patients were asked to rate their symptoms for their complete trauma history instead of for only their worst event.…”
Section: Introductionmentioning
confidence: 99%
“…Lifetime prevalence is estimated at 1.3–12.2% (Karam et al, 2014). The probability of developing PTSD after a traumatic event varies according several risk factors (Hoge, Riviere, Wilk, Herrell, & Weathers, 2014, Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995) which can be classified as pre-trauma (sex, IQ, prior trauma exposure, prior mental disorder, genetics, personality factors), related to trauma (perceived fear of death, assaultive trauma, severity of trauma, physical injury) or post-trauma (high heart rate, low social support, financial stress, pain severity, intensive care stay, traumatic brain injury, peritraumatic dissociation, acute stress disorder, disability; Sareen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the JTOPS study (Shalev et al, 2012) had MVAs, work accidents, physical assaults, terrorist attacks, and other traumas as trauma categories, while the Midwest resilience study (deRoon-Cassini et al, 2010) had MVA, assaults, gunshot wounds, stabbings, falls, work accidents, household accidents, snowmobile accidents, and object-fell-on-person accidents. Based on epidemiological studies showing a higher conditional prevalence of PTSD following interpersonal trauma (Benjet et al, 2016), and categorization of the World Mental Health Survey (Karam et al, 2014), we recoded these variable into (1) MVAs, (2) other non-interpersonal trauma (e.g. work or home accidents, falls, and sports accidents), and (3) interpersonal trauma (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…assaults, rape and other violence). Inconsistently encoded prior trauma exposures, using study-specific instruments, were similarly recoded into categories known to differentially predict PTSD (Karam et al, 2014): ‘interpersonal trauma’ (e.g. war-related events, physical violence, sexual violence, terror, and kidnapping) and ‘all other events’.…”
Section: Methodsmentioning
confidence: 99%